Respiratory Disease Markers in Porcine Bronchoalveolar Lavage Fluid - Hennig‐Pauka, I. (J Vet Med A Physiol Pathol Clin Med, 2007)
In bronchoalveolar lavage fluid (BALF) of pigs originating from different herds bacteria, cells and the antibacterial peptide PR‐39 were examined to gain information about the lung health status. In a high health nucleus herd 56% and in low health herds 20–100% of the examined pigs were found positive for potentially pathogenic bacteria. Based on these findings, a novel definition for bacterial respiratory tract disease was established using an 8% cut‐off for the relative number of neutrophils in bronchoscopic and a 40% cut‐off in transtracheal BALF in combination with the occurrence of potentially pathogenic microorganisms. The antibacterial peptide PR‐39 was highly correlated to this definition of respiratory disease. An assessment of the bacteriological respiratory health status appears to be possibly based on the determination of PR‐39 concentrations in BALF using different cut‐off values according to the lavage method (2.5 nM for bronchoscopic and 5 nM for transtracheal BALF).